Perwujudan Konsep On Pada Tokoh Frieren dan Heiter Dalam Anime Sousou No Frieren Karya Kanehito Yamada - Indriani, Emilia Fortuna; Santoso, Budi (Vocational College of Diponegoro University, 2024)
This study is intended to determine how the embodiment of the value of on, gimu, and giri in the characters Frieren and Heiter in the anime Sousou no Frieren by Kanehito Yamada. The author uses descriptive qualitative method. This research design uses literary anthropology, which leads to literary text research that examines literary reflections as cultural reflections. The data source was taken from Muse Indonesia's Youtube channel video entitled